Digital Literacy as an Effort to Prevent Cyberbullying Among Students: Literasi Digital sebagai Upaya Pencegahan Cyberbullying di Kalangan Siswa - Haniati, Umi; Lestari, Puji; Elsa Indiani, Dea; Khiqmah, Hulasotul; Safarina Zidnad, Lisda; Fairuz Sangadahe, Maily; Angelina Pratiwif, Cilivia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The digital era has made the internet and social media an important part of the lives of teenagers, including high school students in semi-rural areas such as Padamara, Purbalingga Regency. Behind its benefits as a means of learning and communication, low awareness of digital ethics and security increases the risk of cyberbullying. This study aims to analyze the influence of digital literacy on the prevention of cyberbullying in students of SMA Negeri 1 Padamara. The study employed a quantitative approach, utilizing a simple linear regression method, and involved 33 students who had participated in digital literacy training. Digital literacy is measured based on UNESCO's three core competencies, namely the ability to evaluate information, manage digital identity and privacy, and use digital media responsibly. The results showed that digital literacy had a significant and positive effect on cyberbullying prevention, with a regression coefficient of 0.825 and a significance of 0.000 (<0.05). A determination coefficient value (R²) of 0.872 indicates that digital literacy explains 87.2% of the variation in cyberbullying prevention efforts. These findings confirm that strengthening digital literacy competencies in accordance with the UNESCO framework plays a crucial role in shaping safe and ethical online behavior among students. Therefore, schools need to implement digital literacy programs on an ongoing basis to strengthen digital resilience and reduce the potential for cyberbullying in the educational environment.